Advanced Power Battery Management Structure for Electric Vehicles: Design and Implementation (International Journal of Food and Nutritional Sciences, 2022)
This research presents a novel power battery management structure (BMS) specifically designed forelectric vehicles (EVs). The BMS consists of various modules including a central control module,measurement and control module, battery pack, motor controller, direct-current motor, vehicle-mountedcharger, current and electric quantity detection module, vehicle-mounted liquid crystal display module,switching group, memory module, clock module, and temperature management module